The irrationality of technique. Approaches to the concepts of myth and charismatic leader in Carl Schmitt - García Vásquez, Lily (Estudios de Filosofía, 2018)
This article seeks to problematize the concepts of myth and charismatic leader in Carl Schmitt’s work, presenting them as fundamental axes in the understanding of the author’s critique to liberalism and, at the same time, pointing out the underlying contradiction in the apparent irrationalism of these concepts and its becoming pure technique within Schmittian political theory.